Penerapan Model Discovery Learning dalam Meningkatkan Motivasi dan Hasil Belajar Siswa pada Pelajaran IPA SMK Swasta Kristen Tomosa 1 Tahun Pelajaran 2023/2024 - Forisman Zebua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Low student motivation and learning outcomes in science subjects remain major challenges in the learning process, particularly because classroom instruction tends to be teacher-centered and does not actively engage students. This study aimed to analyze the implementation of the Discovery Learning model in improving students’ motivation and learning outcomes in science subjects at SMK Swasta Kristen Tomosa 1 during the 2023/2024 academic year. This study employed a Classroom Action Research (CAR) approach conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects consisted of 35 tenth-grade students. Research data were collected through observation, learning motivation questionnaires, interviews, documentation, and learning achievement tests. The data were analyzed using descriptive quantitative and qualitative techniques through percentages, mean scores, and action hypothesis testing. The findings revealed that the implementation of Discovery Learning improved the quality of the learning process, students’ learning motivation, and learning outcomes. The percentage of learning motivation increased from 64.22% in Cycle I to 91.35% in Cycle II, while the average learning outcomes improved from 62.63 to 82.37 with a learning mastery level reaching 88.57%. These findings indicate that Discovery Learning was effective in creating a more active, meaningful, and student-centered science learning environment.